The church in Antioch in the first century CE : communion and conflict - Slee, Michelle (Journal for the study of the New Testament. Supplement series ;, 2003)
The book explores the problems faced by the church in Antioch in the mid-first century CE once the decision was taken to welcome Gentiles into the church. Slee argues that a particular problem was the celebration of the Eucharist, since some Jewish Christians felt that the table-fellowship this involved inevitably brought the risk of contamination (because of Gentile contact with idolatry). She suggests this was the subject debated at the Jerusalem conference described in Acts 15 and Galatians 2, and it was the eventual decision of the Antioch church to hold separate Eucharists that led to Pau.